PEMANFAATAN SUMUR MINYAK TUA SISA EKSPLOITASI PENINGGALAN BELANDA DALAM HUBUNGANNYA DENGAN PEREKONOMIAN MASYARAKAT DI KABUPATEN MUSI BANYUASIN - Yuswalina, Yuswalina; Candra, Adi (Program Studi Muamalah Fakultas Syariah dan Hukum, 2017)
Indonesia is one country that has a vast area, has a mineral content and is rich in natural resources. A natural resource (both renewable and non-renewable) is an essential resource for human survival. Loss or reduction in the availability of these resources will have an enormous impact to the survival of the human race on earth